Workshop Pembuatan Media Pembelajaran Inovatif Bagi Guru SMP di Kabupaten Takalar - Fathahillah; Riana Tangkin Mangesa; Rachmaniar; Muh Zainuddin R Kasau (Vokatek: Jurnal Pengabdian Masyarakat, 2023)
Learning media are facilities or tools used in the learning process to assist teachers in conveying information and learning materials to students. Learning media can be electronic media, such as video, audio and presentations, as well as non-electronic media, such as books, pictures and real objects. The use of learning media in the classroom can help students understand and remember learning information more easily and effectively, as well as increase student interaction and learning motivation. Apart from that, the use of learning media can also increase the efficiency of the learning process in the classroom and help teachers manage learning time more effectively. Based on the results of initial observations carried out in Takalar Regency, the research team found that the available learning tools did not fully support the achievement of learning objectives. There are still shortcomings in developing and using concepts and implementing innovative and interactive media. In fact, the use of learning media in class can help students understand and remember learning information more easily and effectively, as well as increase student interaction and learning motivation. It is considered important to develop teacher competency in Takalar district so that training is held which is expected to improve teachers' abilities in developing more innovative and effective teaching techniques so that they can improve the quality of learning in the classroom and achieve the desired learning goals.